Small scale experiment study on burning characteristics for in-situ burning of crude oil on open water. (July 2019) - Kong, Depeng; He, Xu; Khan, Faisal; Chen, Guoming; Ping, Ping; Yang, Hanbing; Peng, Rongqi
Abstract: In order to improve the understanding of the burning behavior for the in-situ burning of the spilled crude oil on water, the influence of the oil pool diameter and oil layer thickness of pool fire on open water were studied in relation to the flame height, boilover, and burning efficiency. A series of experiments were conducted in a specially designed experimental setup which could simulate the boundary conditions of the actual ISB operation on water. Three quartz tubes with different diameters and three initial oil layer thicknesses were set as the initial conditions in this study. The results showed that the burning process of oil pool fire on open water could be divided into four stages which are growth stage, quasi-steady stage, decay stage and extinguishing stage. The average flame height of quasi-steady stage increased with oil pool diameter but was little influenced by the initial oil layer thickness. Boilover phenomena were observed in the experiment processes when the oil pool diameter was 150 mm, which showed much later boilover onset time, longer boilover duration and higher average flame height than that for the same size oil paool fire in steel vessel with water sublayer. The burning efficiencies increased with the initial oil layer thicknesses for a given oil pool diameter, which could be explained as the thermal insulation of oil layer. All of the burning efficiencies on experimental dimensions are below 65%, owing to the significant cooling effect of the large amount of water surrounding the burning system. Graphical abstract: Image 1 Highlights: The purpose of the experimental apparatus is to simulate the boundary conditions of ISB. The great differences between oil pool fire on open water and in the limited vessel are considered. The boilover phenomenon is discussed in this study compared with pool fire in limited vessel.